Managing digital servitization toward smart solutions : Framing the connections between technologies, business models, and ecosystems - Kohtamäki, Marko; Rabetino, Rodrigo; Parida, Vinit; Sjödin, David; Henneberg, Stephan (Elsevier, 2022)
The present study extends the discussion on product manufacturers' digital servitization toward smart solutions by outlining and reviewing the existing literature on digital servitization and smart solutions. We focus on potential configurations based on technologies, business models, and ecosystems to understand how this transition can be managed through the process of reconfiguration. We define smart solutions as an advanced state of product-service-software systems, and we use moving vehicles as a case in point. We base our discussion on a configurational research approach, examining the role of advanced technologies (e.g., artificial intelligence), novel business models, and modern ecosystems (e.g., platforms and innovation ecosystems) in shaping digital servitization toward smart and autonomous solutions. We identify gaps in the literature, offer an analytical framework, suggest avenues for future research, and contribute by laying the theoretical foundations and proposing managerial directions for a digital servitization journey toward smart solutions. By so doing, we present the papers accepted to the current IMM special issue on “Moving toward autonomous solutions: The role of Product-Service-Software Systems”, which this review article introduces.
Keywords: Artificial intelligence (AI) and autonomous solutions; Business model configurations and business model innovation; Digital servitization; Platforms and sustainability; Smart product-service systems (PSS) and smart solutions; fi=Strateginen johtaminen|en=Strategic Management|